(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The essential elements of the SEBI (Portfolio Managers) Regulations, 2020 are discussed in this article. It attempts to examine this new legal reform and all of the significant changes that it contains. It also aims to determine how these changes will affect the sector and whether or not they will be advantageous to investors. SEBI (Portfolio Managers) Regulations, 2020 is a significant step forward in incorporating market and investor needs into the regulatory framework. This study examines the significant changes brought about by the new reform. It also suggests some additional areas where the regulator should focus during the implementation phase. The new PMS Regulations provide more transparency and consistency for the PMS business. Clients of PMS will be able to better comprehend and compare the terms of various Portfolio Managers’ services.